The mountain chant : a Navajo ceremony - Matthews, Washington, 1843-1905 (University of Utah Press, 1997)
"The Mountain Chant is a nine-day Navajo healing ceremony, one of several major rites undertaken only in winter. Aside from curing disease, it brings rain and invokes the unseen powers for general benefit. Though perhaps practiced less often now than better-known ceremonies such as the Night Chant, it is by no means forgotten." "Fully faithful to the original published by Washington Matthews over a century ago, this edition contains the story of the wandering hero upon whose exploits the Mountain Chant is based, a description of each of the nine ceremonial days, and original song texts and translations."--Jacket